The Effect of Expressive Writing Therapy on Self-Efficacy and Subjective Well-Being Students - Rizka Mianti; Hasanuddin Hasanuddin; Salamiah Sari Dewi (Borong Newinera Publisher, 2024)
High academic pressure, personal obstacles, and the challenges brought by the pandemic can lead to stress and diminished self-confidence in students. In this context, self-efficacy and subjective well-being emerge as crucial factors influencing the learning process. Barriers such as a lack of outlets for expressing emotions and difficulties in overcoming problems can impede students' academic journey. This research conducted at SMA Negeri 1 Bangun Purba aims to examine the impact of expressive writing therapy on students' self-efficacy and subjective well-being. The study involves the development of an expressive writing therapy module, incorporating a scale with validated and reliable measures. The application of this therapy to students follows a quasi-experimental method using a nonequivalent control group design. The research sample consists of two groups: an experimental group subjected to expressive writing therapy and a control group. The results indicate that in the control group, there is no significant difference in self-efficacy (Wilcoxon test, p=0.0798) and subjective well-being (t-test, p=0.3691) before and after the post-test. However, in the experimental group, a significant difference is observed in both self-efficacy (t-test, p<0.05) and subjective well-being (Wilcoxon test, p<0.05). Simultaneously, both aspects can be enhanced through expressive writing therapy (MANOVA, p<0.05). This research highlights that the developed expressive writing therapy module effectively improves students' self-efficacy and subjective well-being.